Acute effect of biomechanical foot orthotics on gross efficiency in cyclists affected by an anatomic asymmetry in time trial position - Bouillod, A.; Retali, M.; Soto-Romero, G.; Brunet, E.; Frémeaux, M.; Cassirame, J.; Maillot, J.; Grappe, F. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
Cyclist position on his bicycle and individual anthropometric parameters are very important to optimise pedalling biomechanics (Bini et al. 2011). Postural imbalance can lead to increase joint stress in the lower limbs. Therefore, different methods are used to reduce these joint stresses such as chiropractic, kinesio taping or the use of foot orthotics. The latter seem to be of interest to reduce parasitic movements during the pedalling cycle (e.g. pelvis tilt) and to restore the symmetry of the movements, both during the pushing and pulling phases of the pedal.